APLIKASI TEKNOLOGI BUDIDAYA TANAMAN PAKAN RAMAH LINGKUNGAN TERHADAP KUALITAS HIJAUAN (Studi Pemanfaatan Pupuk Organik Kascing dan Sistem Tanam) - I Wayan Suarna (Environmental Research Center (PPLH) of Udayana University)
Chemical analysis of forages was conducted at Animal nutrition Laboratory,Faculty of Animal Husbandry Udayana University to study the effect of castingorganic fertilizer on Quality in Grass-legume Association.Field experiment was consisted of two factors as follows: (1) three types ofcropping systems (grass monoculture, legume monoculture, and grass-legumeassociation), (2) four levels of casting organic fertilizer (0, 10, 20, and 30 t ha-1).The experiment design was a randomized block design arranged in factorial patternand was replicated three times.The results showed chemical compossition of forage in association system at20 t ha-1 casting had a higher quality and a higher Ca and P contents, a lower NDFand lignin contents, whereas : ADF, hemisellulose, and cellulose contents were notsignificantly different.